Carbon gold rush and carbon cowboys: a new chapter in green mythology? - Nerlich, Brigitte; Koteyko, Nelya (Taylor and Francis, 2010)
Individual and collective efforts to mitigate climate change in the form of carbon offsetting and emissions trading schemes have recently become the focus of much media attention. In this paper we explore a subset of the UK national press coverage centered on such schemes. The articles, selected from general as well as specialized business and finance newspapers, make use of gold rush, Wild West and cowboy imagery which is rooted in deeply entrenched myths and metaphors and allows readers to make sense of very complex environmental, political, ethical, and financial issues associated with carbon mitigation. They make what appears complicated and unfamiliar, namely carbon trading and offsetting, seem less complex and more familiar. A critical discussion of this type of imagery is necessary in order to uncover and question tacit assumptions and connotations which are built into it and which might otherwise go unnoticed and unchallenged in environmental communication.